2011
DOI: 10.1007/s12257-011-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and immunostimulating activity of a water-soluble polysaccharide isolated from Haematococcus lacustris

Abstract: A water-soluble polysaccharide was isolated and purified from the culture filtrate of the photosynthetic green microalgae Haematococcus lacustris by 75% ethanol precipitation and Sepharose CL-6B column chromatography. The molecular mass of the purified polysaccharide (named HCP) was estimated to be approximately 135 kDa by sizeexclusion HPLC and its monosaccharide composition was galactose, glucose and mannose at a relative molar ratio of 2.0, 1.0, and 4.1, respectively, suggesting that HCP is a galactomannan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…These observations are enforced by several demonstration of in vitro antimicrobial activity of chitosan depending on the molecular weight, and its degree of deacetylation to other bacterial strains, as earlier study demonstrated (Choi et al 2001;Fernandes et al 2008). For several decades, various applications of HMWC and its hydrolysates with different molecular weights or deacetylation degree were widely focused to investigate their biological activities including antimicrobial (Moon et al 2007;No et al 2002) and immunostimulating (Moon et al 2007;Park et al 2011) activities. However, due to shortcomings of the preparation of chitosan hydrolysates (CTSNs), various studies were performed to establish the best conditions for the high-yield production of the specific size of hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are enforced by several demonstration of in vitro antimicrobial activity of chitosan depending on the molecular weight, and its degree of deacetylation to other bacterial strains, as earlier study demonstrated (Choi et al 2001;Fernandes et al 2008). For several decades, various applications of HMWC and its hydrolysates with different molecular weights or deacetylation degree were widely focused to investigate their biological activities including antimicrobial (Moon et al 2007;No et al 2002) and immunostimulating (Moon et al 2007;Park et al 2011) activities. However, due to shortcomings of the preparation of chitosan hydrolysates (CTSNs), various studies were performed to establish the best conditions for the high-yield production of the specific size of hydrolysates.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the cytotoxicity, RAW264.7 murine macrophages cells (5 × 10 4 cells/well) were suspended in complete RPMI1640 medium, and the proliferation of the cells was assessed in micro-culture tetrazolium viability assay using the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT), using a multi-detection microplate reader (Molecular Devices, Sunnyvale,CA, USA) as described the previous study (Park et al 2011). All experiments for the MTT assay were performed in triplicates.…”
Section: Determination Of Bacterial Susceptibilitymentioning
confidence: 99%
“…Many microalgal polysaccharides possess the ability to modulate the immune system through the activation of macrophage functions and the induction of ROS, nitric oxide, and various other types of cytokines/chemokines [65]. Macrophages are able to regulate several innate responses and secrete cytokines and chemo-cytokines that serve as signals for immune and inflammatory molecular reactions [66]. Sulfated polysaccharides with anti-inflammatory activity can be applied in skin treatments inhibiting the migration and adhesion of polymorphonuclear leukocytes [63].…”
Section: Algal Macromolecules As Bioactive Compounds and Their Physiomentioning
confidence: 99%
“…A glycoprotein prepared from Chlorella vulgaris culture supernatant exhibits protective activity against tumor metastasis and chemotherapy-induced immunosuppression in mice [34]. The sulfated exopolysaccharide of Haematococcus lacustris (H. pluvialis) is reported to have potent early innate immune stimulating activities by enhancing the expression of TNF-α, COX-2 and iNOS in murine macrophage cells [35].…”
Section: Cyanophytamentioning
confidence: 99%